Vaccine information seeking on social Q&A services - Sharon, Aviv J.; Baram-Tsabari, Ayelet; Yom-Tov, Elad (Vaccine, 2020)
Experts are concerned about the spread and recalcitrance of vaccine misinformation and its contribution to vaccine hesitancy. Despite this risk, little research attention has been paid to understanding how individuals seek vaccine information online and evaluate its trustworthiness. Here, we hypothesized that when vaccine-hesitant parents seek information about vaccines, they prefer trustworthy sources based on their competence, integrity and benevolence. We explored this issue using 4910 questions and 2583 answers retrieved from two social question-and-answer (Q&A) platforms: “Yahoo! Answers” and the Facebook group “Talking about Vaccines.” We examined what kinds of questions are asked about vaccines, to what extent they are explicitly directed at health professionals or parents, and what features of the answers predict perceived answer quality, based on the theory of epistemic trust. The findings indicate that on different platforms, vaccine-related questions focus on different topics; namely, questions on one platform focused on the risks and benefits of vaccination, whereas they dealt with vaccine schedules on the other. On both platforms, most questions did not specify that an answer should be based on professional expertise or parents' experience. Both pro-vaccine and anti-vaccine answers were proportionately represented among the “best answers”. However, if an answer was written by a health professional, the askers and the community on “Yahoo! Answers” were twice as likely to choose it as the “best answer” to a vaccine-related question, irrespective of whether it encouraged or discouraged vaccination. By contrast, an online experiment revealed that both the identity of the respondent and the stance towards vaccination affected the perceived trustworthiness of the answers. These findings indicate that despite the proliferation of anti-vaccine messages, epistemic trust in mainstream science and medicine is robust. User responses to expert answers suggest that expert outreach in online environments may be an effective intervention to address vaccine hesitancy.